2018
DOI: 10.1177/1044207318789419
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Participation in School-to-Work Programs on Postsecondary Outcomes for Youth With Disabilities From Low-Income Families

Abstract: Individuals with disabilities who also live in poverty face a double jeopardy. Disability and poverty are each separately associated with poorer education and employment outcomes. One approach to ameliorate these poorer outcomes is to improve the transition from high school to adulthood. Using data from the National Longitudinal Study of Adolescent to Adult Health, this article examines the role of school-to-work training programs on adult outcomes for individuals with disabilities who live in welfare receivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Courses allow students to explore specific occupations within provision which is rich in work-based and work-related learning (Education Council, 2014 [198]). Recent analysis of longitudinal data has shown that students enrolling on such programmes are more likely than comparable peers to enter full-time work soon after completing secondary education, to earn more five years into the labour market and to be working in a profession linked to school courses selected (Misko, 2020[199]) (Ranasinghe, 2019[200]).…”
Section: Quantitative Studies Of Long-term Outcomes Linked To Teenagementioning
confidence: 99%
“…Courses allow students to explore specific occupations within provision which is rich in work-based and work-related learning (Education Council, 2014 [198]). Recent analysis of longitudinal data has shown that students enrolling on such programmes are more likely than comparable peers to enter full-time work soon after completing secondary education, to earn more five years into the labour market and to be working in a profession linked to school courses selected (Misko, 2020[199]) (Ranasinghe, 2019[200]).…”
Section: Quantitative Studies Of Long-term Outcomes Linked To Teenagementioning
confidence: 99%
“…These studies do not particularly consider YPWD. Enayati and Karpur (2018) examine how participation in social policy programs with a focus on the STWT can generally support YPWD from welfare-receiving households. They find that participation leads to higher employment rates and lower criminal behavior but also to lower wages.…”
Section: Previous Researchmentioning
confidence: 99%
“…This applies particularly to disadvantaged youth such as those with disabilities and those from poor families (Osgood et al, 2005). Thus, the school-to-work transition (STWT) for those with disabilities from low-income families is twice as challenging (Enayati & Karpur, 2018). This is particularly relevant, as studies on the STWT often neglect persons with disabilities as a group.…”
Section: Introductionmentioning
confidence: 99%
“…These kinds of programmes are common in Australia, Canada, and the United States. In Australia, a majority of schools offer young people between the ages of 16 and 18 the opportunity to study such provision (Education Council, 2014 [48]). In the United States, such programmes expanded particularly during the 1990s, and by 2002, 60% of young people undertook at least one career exploratory course of study within their High School curricula (Visher, 2004[49]).…”
Section: Occupationally-focused Short Programmes and Their Relationship With Adult Employment Outcomesmentioning
confidence: 99%